Rancang Bangun Aplikasi Pengelolaan Pembelian Bahan Baku Pada PT. Indochito International Sidoarjo - Arista Arista; Vivine Nurcahyawati; Tony Soebijono (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Management of purchase of raw materials is a very important activity in the PT. INDOCHITO International for supporting the availability of raw materials in the production of PT. INDOCHITO International. Calculation error occurred, the problems in the reporting process, recaps mistakes and the absence of evidence of storage media - evidence of transactions, they often occur in the PT. INDOCHITO International Sidoarjo. To solve the above problems, the storage medium, recording purchases and reporting processes used to a computerized system. To meet these needs has to be developed raw material purchase management application at PT. INDOCHITO International. Once tested, raw material purchase management applications can help the process of calculating, can help the process of reporting and perekapan stocks of raw materials and the availability of storage media proof of purchase ever by the company. Keywords: Applications, Purchase Management, Raw Material